Development Of Interactive Media Based On Articulated Storyline 3 In Science Subjects At SDN Kepanjen 2 - Fanani, Moh Alfian; Rusmawati, Retno Danu; Rahman, Ujang (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research is motivated by the science learning process in grade VI of SDN Kepanjen 2 which is still teacher-centered and lacks the use of interesting learning media for students. This can have an impact on the low motivation and interest of students in learning, as well as their understanding of science materials. In addition, teachers also still have difficulty in developing innovative and interactive learning media, especially learning media based on articulated storyline 3. This development research aims to develop interactive learning media based on Articulated Storyline 3 (AS3) in science subjects at SDN Kepanjen 2 Jombang. This research uses the Research & Development (R&D) development model with an ADDIE design which consists of analysis, design, development, implementation, and evaluation stages. The results show that the interactive learning media based on AS3 developed is very feasible to use with a feasibility percentage of 95.29% based on the assessment of media experts, design experts, material experts, and peers. The results of trials on students show that this learning media is effective to use with an effectiveness percentage of 88.00% and the completeness of learning outcomes reaches 86.67%. Thus, interactive learning media based on AS3 in science subjects on the material of exploring the solar system is feasible and effective to use in learning in grade VI Elementary School.